100-year drought - fact or fiction? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
100-year drought - fact or fiction? Members of the United Nations Intergovernmental Panel on Climate Change have been meeting in Montreal to discuss the implications that global warming is no longer a matter of speculation, but of fact. Computer...